EXPECTATIONS OF A MEDICAL STUDENT: THE DEFICIT BETWEEN '˜WHAT IS' AND '˜WHAT SHOULD BE' - Rasool, Ahsan; Rasool, Maleeha; Farooq, Umer; Ahmad, Ashfaq; Tariq, Sumbal; Saeed, Sabir; Shah, Saliman; Manan, Zainab; Ahmad, Fiaz; Haidar, Ali Mohammed Yahya (Journal of Ayub Medical College Abbottabad, 2013)
Background: Over past few decades, the expectations of medical students about their academics, extracurricular support from college and about their social life at campus have all been changed greatly.The relative scarcity of data about the expectations of Pakistani medical students has merited this study. Method: A cross-sectional survey was undertaken at Ayub Medical College, Abbottabad at the in December, 2012 based on random sampling technique. Expectation questionnaire of University of Northumbria for Survey of Student Attitudes, Experiences and Expectations was used. Results: One hundred and sixty-two students responded to the questionnaire with 93 (58.1%) males. Students had a fairly realistic picture of academic demands and college environment. There was major difference in the opinions of male and female students about physical environment of college with female having prior misconception about it. Forty-eight percent student found medical education challenging. About 63.3% students had realistic picture about study habits needed in the college. About 77.9% and 73.8% students had reasonable picture of academic staff and teaching methods at the college respectively. Students had a fair picture of the thorough help from teachers. About 63.5% students seemed well-prepared for the extent to which they would need to be independent learners at medical college. However expectations of 55.6% students about non-academic support were higher than provided. Also only 20.3% students found social adjustments easier than expected. About 39.5% students had fairly accurate expectations regarding the physical environment of the college; however in gender based comparison, about 55% female students felt being mistaken about the environment. Conclusion: Academic demands are fairly in accordance with the expectations of students. However there is a need to make course content interesting and more understandable. Also the extracurricular support in form of various facilities should be bolstered. Most importantly, the physical environment needs to be made more amicable especially for female students. Keywords: expectations, medical students, academic demands, facilities, social adjustment